Influence of interrupted versus continuous suture technique on intestinal anastomotic leakage rate in patients with Crohn’s disease — a propensity score matched analysis - Mittelstädt, Anke; von Löffelholz, Tobias; Weber, Klaus; Denz, Axel; Krautz, Christian; Grützmann, Robert; Weber, Georg; Brunner, Maximilian (International Journal of Colorectal Disease, 2022)
Purpose: Intestinal anastomosis is a crucial step in most intestinal resections, as anastomotic leakage is often associated with severe consequences for affected patients. There are especially two different techniques for hand-sewn intestinal anastomosis: the interrupted suture technique (IST) and the continuous suture technique (CST). This study investigated whether one of these two suture techniques is associated with a lower rate of anastomotic leakage. Methods: A retrospective review of 332 patients with Crohn’s disease who received at least one hand-sewn colonic anastomosis at our institution from 2010 to 2020 was performed. Using propensity score matching 183 patients with IST were compared to 96 patients with CST in regard to the impact of the anastomotic technique on patient outcomes. Results: Overall anastomotic leakage rate was 5%. Leakage rate did not differ between the suture technique groups (IST: 6% vs. CST: 3%, p = 0.393). Multivariate analysis revealed the ASA score as only independent risk factor for anastomotic leakage (OR 5.3 (95% CI = 1.2–23.2), p = 0.026). Suture technique also showed no significant influence on morbidity and the re-surgery rate in multivariate analysis. Conclusion: Our data suggest that the chosen suture technique (interrupted vs. continuous) has no influence on postoperative outcome, especially on anastomotic leakage rate. This finding should be confirmed by a randomized controlled trial.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Anastomotic leakage; Continuous suture technique; Crohn’s disease; Interrupted suture technique; Intestinal anastomosis